β-THALASSEMIA TRAIT MENGGUNAKAN ELEKTROFORESIS MIKROKAPILER - Nuryanti Nuryanti; Ratna Akbari Ganie; Adi Koesoema Aman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Thalassemia is a genetic disorder disease which spread in the different parts of the world, including Indonesia. The incidence of β-thalassemia trait in Indonesia is between 3−8%. The objective of this study is to know the incidence of β-thalassemia trait in studentswho performed medical check-up, which obtain by using capilary electrophoresis, to describe the characteristics and to obtain theaverage value, of MCV, MCH and HbA2. This study was an observational study by cross-sectional method, which was carried out at theDepartment of Clinical Pathology Haji Adam Malik Hospital in Medan, performed on July to September 2012, consisting of 560 subjects.The examination included FBC to get a microcytic hypochromic sample (MCV <80 fl, MCH <27 pg), then a quantification of HbA2from microcytic hypochromic sample was done using electrophoresis. From the 560 samples 54% were male and other 46% were female.The average age was 19.25±0.25 years, the percentage based on the races tribe, which including Bataknesse 57.78%, Javanesse 15.74%,Acehnesse 10.73, Malay 9.12%, Karonesse 3.93%, Padangnesse 2.32% and Nias 0.35%. The average of the hematological indices, in the50 subjects were 71.63±7.68 for MCV and 23.27±2.85 for MCH. The quantification of HbA2 in micrositic hypochromic subject showed10 β-thalassemia trait subject (1.8%) with average of HbA2 (4.34±0.25), MCV (62.66±3.41), and MCH (20.11±2.18) as well as four(4) hemoglobin E subjects (0.7%). Based on this performed research on 560 students with the incidence of β-Thalassemia Trait was 1.8%with the average of HbA2 quantification was 4.34±0.25.